Inland Treatment of the Brine Generated from Reverse Osmosis Advanced Membrane Wastewater Treatment Plant Using Epuvalisation System - Qurie, Mohannad (2013)
The reverse osmosis (RO) brine generated from the Al-Quds University wastewater treatment plant was treated using an epuvalisation system. The advanced integrated wastewater treatment plant included an activated sludge unit, two consecutive ultrafiltration (UF) membrane filters (20 kD and 100 kD cutoffs) followed by an activated carbon filter and a reverse osmosis membrane. The epuvalisation system consisted of salt tolerant plants grown in hydroponic channels under continuous water flowing in a closed loop system, and placed in a greenhouse at Al-Quds University. Sweet basil (Ocimum basilicum) plants were selected, and underwent two consecutive hydroponic flowing stages using different brine-concentrations: an adaptation stage, in which a 1:1 mixture of brine and fresh water was used; followed by a functioning stage, with 100% brine. A control treatment using fresh water was included as well. The experiment started in April and ended in June (2012). At the end of the experiment, analysis of the effluent brine showed a remarkable decrease of electroconductivity (EC), PO43−, chemical oxygen demand (COD) and K+ with a reduction of 60%, 74%, 70%, and 60%, respectively, as compared to the influent. The effluent of the control treatment showed 50%, 63%, 46%, and 90% reduction for the same parameters as compared to the influent. Plant growth parameters (plant height, fresh and dry weight) showed no significant difference between fresh water and brine treatments. Obtained results suggest that the epuvalisation system is a promising technique for inland brine treatment with added benefits. The increasing of channel number or closed loop time is estimated for enhancing the treatment process and increasing the nutrient uptake. Nevertheless, the epuvalisation technique is considered to be simple, efficient and low cost for inland RO brine treatment.